How Does It Feel to Be Online? Psychotherapists’ Self-Perceptions in Telepsychotherapy Sessions During the COVID-19 Pandemic in Italy - Mancinelli, Elisa; Gritti, Emanuela S.; Schiano Lomoriello, Arianna; Salcuni, Silvia; Lingiardi, Vittorio; Boldrini, Tommaso (Frontiers in Psychology, 2021)
Aims: The COVID-19 pandemic and consequent extreme restrictions imposed by governments across the world forced psychotherapists to abruptly change their working modality. The first aim of the current study was to assess psychotherapists’ self-perceptions (i.e., affective and cognitive perceptions about their self and their self in relation to clients) when providing telepsychotherapy during the first peak of the COVID-19 pandemic in Italy. The second aim was to explore the associations between psychotherapists’ self-perceptions, characteristics, and clinical practices. Method: An online survey was administered to 281 Italian licensed psychotherapists (Mage = 45.15; SD = 10.2; 83.6% female) between April 5 and May 10, 2020. The survey comprised ad-hoc questions that were designed to collect sociodemographic details and information related to working practices. Moreover, a semantic differential (SD) scale was developed to assess psychotherapists’ self-perceptions, and a factor analysis was performed from the SD items. Results: The SD scale showed an overall trend of positive psychotherapist self-perception during telepsychotherapy, despite reports of greater fatigue and directive and talkative behavior during sessions. Four SD factors accounted for 45% of the variance: “Affective Availability,” “Attitude Predisposition,” “Well-being,” and “Interventionism.” Scores on the first three factors were indicative of psychotherapists’ Positive versus Negative self-perception. A comparison of the Positive and Negative attitudinal profiles using the chi-squared test with Yates’s correction and a Monte Carlo simulation found that psychotherapists with a Positive profile reported greater satisfaction with the telematic modality and were more likely to perceive that their clients were able to maintain privacy during sessions. Conclusions: The results suggest that Italian psychotherapists have been able to promptly adapt to the imposed telematic modality during the COVID-19 pandemic. However, they may have attempted to compensate for their physical distance from clients by intervening more during sessions. These findings may support psychotherapists who are currently practicing and inform future practitioners who are considering the use of telematic treatment as a routine component of psychotherapeutic care.